Oral Blue Nevus two case reports and literature review. - Silva, Larissa; Martins da Cruz, Timilly Mayra; Aparecido Gonçalves , Moisés Willian; Moreira Gonçalves , Rafaela Nogueira; Rocha dos Santos , Cássio Roberto; Marques Mesquita , Ana Terezinha (Revista Estomatología, 2021)
Case Description We report two cases of oral Blue Nevus. The first case is a 32 years old female patient with a brown-blue lesion on hard palate, with no clinical symptoms that has always been present but that recently has been growing. The case is 36 years old male patient with a brown macule on hard palate.Clinical Findings On case report 1, oral examinations revealed an irregular brown-blue macule, measuring 13 x 6mm on hard palate. On case report 2, oral examination showed an oval brownish macule also located on hard palate.Treatment and Outcome: Excisional biopsy was performed in both cases and histopathology analyses revealed diagnosis of Blue Nevus.Clinical Relevance Diagnosis of pigmented lesions of the oral cavity can be challenging once there are a variety of causes such as racial pigmentation, systemic diseases, use of medication, metal tattooing melanocytic nevus, melanoacanthoma, and melanoma. The correct diagnosys is important to conduct the best management of these lesions, especially the ones with malignancy potential.